A defined metabolic state in pre B cells governs B-cell development and is counterbalanced by Swiprosin-2/EFhd1 - Stein, Merle; Dütting, Sebastian; Mougiakakos, Dimitrios; Boesl, Michael R.; Fritsch, Kristin; Reimer, Dorothea; Urbanczyk, Sophia; Steinmetz, Tobit; Schuh, Wolfgang; Bozec, Aline; Winkler, Thomas; Jäck, Hans-Martin; et al. (Cell Death and Differentiation, 2017)
B-cell development in the bone marrow comprises proliferative and resting phases in different niches. We asked whether B-cell metabolism relates to these changes. Compared to pro B and small pre B cells, large pre B cells revealed the highest glucose uptake and ROS but not mitochondrial mass, whereas small pre B cells exhibited the lowest mitochondrial membrane potential. Small pre B cells from Rag1;33.C9 μ heavy chain knock-in mice revealed decreased glycolysis (ECAR) and mitochondrial spare capacity compared to pro B cells from Rag1 mice. We were interested in the step regulating this metabolic switch from pro to pre B cells and uncovered that Swiprosin-2/EFhd1, a Ca-binding protein of the inner mitochondrial membrane involved in Ca-induced mitoflashes, is expressed in pro B cells, but downregulated by surface pre B-cell receptor expression. Knockdown and knockout of EFhd1 in 38B9 pro B cells decreased the oxidative phosphorylation/glycolysis (OCR/ECAR) ratio by increasing glycolysis, glycolytic capacity and reserve. Prolonged expression of EFhd1 in EFhd1 transgenic mice beyond the pro B cell stage increased expression of the mitochondrial co-activator PGC-1α in primary pre B cells, but reduced mitochondrial ATP production at the pro to pre B cell transition in IL-7 cultures. Transgenic EFhd1 expression caused a B-cell intrinsic developmental disadvantage for pro and pre B cells. Hence, coordinated expression of EFhd1 in pro B cells and by the pre BCR regulates metabolic changes and pro/pre B-cell development.Cell Death and Differentiation advance online publication, 19 May 2017; doi:10.1038/cdd.2017.52.

A pair of non‐competing neutralizing human monoclonal antibodies protecting from disease in a SARS‐CoV‐2 infection model - Peter, Antonia Sophia; Roth, Edith; Schulz, Sebastian; Fraedrich, Kirsten; Steinmetz, Tobit; Damm, Dominik; Hauke, Manuela; Richel, Elie; Müller-Schmucker, Sandra; Habenicht, Katharina Marie; Eberlein, Valentina; Issmail, Leila; et al. (European Journal of Immunology, 2021)
TRIANNI mice carry an entire set of human immunoglobulin V region gene segments and are a powerful tool to rapidly isolate human monoclonal antibodies. After immunizing these mice with DNA encoding the spike protein of SARS-CoV-2 and boosting with spike protein, we identified 29 hybridoma antibodies that reacted with the SARS-CoV-2 spike protein. Nine antibodies neutralize SARS-CoV-2 infection at IC50 values in the subnanomolar range. ELISA-binding studies and DNA sequence analyses revealed one cluster of three clonally related neutralizing antibodies that target the receptor-binding domain and compete with the cellular receptor hACE2. A second cluster of six clonally related neutralizing antibodies bind to the N-terminal domain of the spike protein without competing with the binding of hACE2 or cluster 1 antibodies. SARS-CoV-2 mutants selected for resistance to an antibody from one cluster are still neutralized by an antibody from the other cluster. Antibodies from both clusters markedly reduced viral spread in mice transgenic for human ACE2 and protected the animals from SARS-CoV-2-induced weight loss. The two clusters of potent non-competing SARS-CoV-2 neutralizing antibodies provide potential candidates for therapy and prophylaxis of COVID-19. The study further supports transgenic animals with a human immunoglobulin gene repertoire as a powerful platform in pandemic preparedness initiatives.

A surrogate cell-based SARS-CoV-2 spike blocking assay - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Stefan; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al. (European Journal of Immunology, 2021)
To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and successful vaccination against coronavirus disease 2019 (COVID-19), the kinetics of neutralizing or blocking anti-SARS-CoV-2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive surrogate SARS-CoV-2 blocking assay (SUBA) using immobilized recombinant human angiotensin-converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS-CoV-2 spike protein. Spike protein-expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell-associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2- or 3-approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell-bound SARS-CoV-2 spike protein and can be rapidly adjusted to quickly pre-screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS-CoV-2 variants.
CRIS-Team Scopus Importer:2021-10-08
Keywords: COVID-19; hACE2; SARS-CoV-2; Spike protein; Surrogate blocking assay

B Cell Speed and B-FDC Contacts in Germinal Centers Determine Plasma Cell Output via Swiprosin-1/EFhd2 - Reimer, Dorothea; Meyer-Hermann, Michael; Rakhymzhan, Asylkhan; Steinmetz, Tobit; Tripal, Philipp; Thomas, Jana; Böttcher, Martin; Mougiakakos, Dimitrios; Schulz, Sebastian; Urbanczyk, Sophia; Hauser, Anja E.; Niesner, Raluca A.; et al. (Cell Reports, 2020)
Plasma cells secreting affinity-matured antibodies develop in germinal centers (GCs), where B cells migrate persistently and directionally over defined periods of time. How modes of GC B cell migration influence plasma cell development remained unclear. Through genetic deletion of the F-actin bundling protein Swiprosin-1/EF-hand domain family member 2 (EFhd2) and by two-photon microscopy, we show that EFhd2 restrains B cell speed in GCs and hapten-specific plasma cell output. Modeling the GC reaction reveals that increasing GC B cell speed promotes plasma cell generation. Lack of EFhd2 also reduces contacts of GC B cells with follicular dendritic cells in vivo. Computational modeling uncovers that both GC output and antibody affinity depend quantitatively on contacts of GC B cells with follicular dendritic cells when B cells migrate more persistently. Collectively, our data explain how GC B cells integrate speed and persistence of cell migration with B cell receptor affinity.
CRIS-Team Scopus Importer:2020-08-14
Keywords: actin cytoskeleton; B cell receptor; differentiation; follicular dendritic cell; germinal center; migration; plasma cell; selection; Swiprosin-1/EFhd2; synapse

Guidelines for the use of flow cytometry and cell sorting in immunological studies - Cossarizza, Andrea; Chang, Hyun-Dong; Radbruch, Andreas; Akdis, Mubeccel; Andrae, Immanuel; Annunziato, Francesco; Bacher, Petra; Barnaba, Vincenzo; Battistini, Luca; Bauer, Wolfgang M.; Baumgart, Sabine; Becher, Burkhard; et al. (European Journal of Immunology, 2017)
EVALuna2:13453

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Identification of TFG- and Autophagy-Regulated Proteins and Glycerophospholipids in B Cells - Steinmetz, Tobit; Thomas, Jana; Reimann, Lena; Himmelreich, Ann-Kathrin; Schulz, Sebastian; Golombek, Florian; Castiglione, Kathrin; Jäck, Hans-Martin; Brodesser, Susanne; Warscheid, Bettina; Mielenz, Dirk (Journal of Proteome Research, 2024)
Keywords: metabolism; lysosome; JCHAIN; immunoglobulin; TRK-fused gene; ribosome; plasma cell; phosphatidylglycerol; autophagy; BCL10; endoplasmic reticulum stress; autophagy flux; B cell

Influence of Swiprosin2/EFhd1 on the metabolic control of B cell differentiation and humoral immunity - Urbanczyk, Sophia; Stein, Marcello F.; Duetting, S.; Mougiakakos, Dimitrios; Boesl, M.; Reimer, Dorothea; Steinmetz, Tobit; Schuh, Wolfgang; Bozec, Aline; Winkler, Thomas; Jäck, Hans-Martin; Mielenz, Dirk (2017)
EVALuna2:13653

Krüppel-like factor 2 controls IgA plasma cell compartmentalization and IgA responses - Wittner, Jens; Schulz, Sebastian; Steinmetz, Tobit; Berges, Johannes; Hauke, Manuela; Channell, William M.; Cunningham, Adam F.; Hauser, Anja E.; Hutloff, Andreas; Mielenz, Dirk; Jäck, Hans-Martin; Schuh, Wolfgang (Mucosal Immunology, 2022)
Krüppel-like factor 2 (KLF2) is a potent regulator of lymphocyte differentiation, activation and migration. However, its functional role in adaptive and humoral immunity remains elusive. Therefore, by using mice with a B cell-specific deletion of KLF2, we investigated plasma cell differentiation and antibody responses. We revealed that the deletion of KLF2 resulted in perturbed IgA plasma cell compartmentalization, characterized by the absence of IgA plasma cells in the bone marrow, their reductions in the spleen, the blood and the lamina propria of the colon and the small intestine, concomitant with their accumulation and retention in mesenteric lymph nodes and Peyer’s patches. Most intriguingly, secretory IgA in the intestinal lumen was almost absent, dimeric serum IgA was drastically reduced and antigen-specific IgA responses to soluble Salmonella flagellin were blunted in KLF2-deficient mice. Perturbance of IgA plasma cell localization was caused by deregulation of CCR9, Integrin chains αM, α4, β7, and sphingosine-1-phosphate receptors. Hence, KLF2 not only orchestrates the localization of IgA plasma cells by fine-tuning chemokine receptors and adhesion molecules but also controls IgA responses to Salmonella flagellin.
CRIS-Team Scopus Importer:2022-04-15

Mitochondrial metabolism influences plasma cell differentiation - Urbanczyk, Sophia; Baris, O.; Reimer, Dorothea; Steinmetz, Tobit; Mougiakakos, Dimitrios; Wiesner, R.; Mielenz, Dirk (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle

Regulation of plasma cell homeostasis and antibody secretion through modulation of autophagy and endoplasmic reticulum stress by Trk-fused-gene (TFG) - Thomas, Jana; Steinmetz, Tobit; Mielenz, Dirk (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

TFG is required for autophagy flux and to prevent endoplasmic reticulum stress in CH12 B lymphoma cells - Steinmetz, Tobit; Schlötzer-Schrehardt, Ursula; Hearne, Abigail; Schuh, Wolfgang; Wittner, Jens; Schulz, Sebastian; Winkler, Thomas; Jäck, Hans-Martin; Mielenz, Dirk (Autophagy, 2020)
Plasma cells depend on quality control of newly synthesized antibodies in the endoplasmic reticulum (ER) via macroautophagy/autophagy and proteasomal degradation. The cytosolic adaptor protein TFG (Trk-fused gene) regulates ER-Golgi transport, the secretory pathway and proteasome activity in non-immune cells. We show here that TFG is upregulated during lipopolysaccharide- and CpG-induced differentiation of B1 and B2 B cells into plasmablasts, with the highest expression of TFG in mature plasma cells. CRISPR-CAS9-mediated gene disruption of tfg in the B lymphoma cell line CH12 revealed increased apoptosis, which was reverted by BCL2 but even more by ectopic TFG expression. Loss of TFG disrupted ER structure, leading to an expanded ER and increased expression of ER stress genes. When compared to wild-type CH12 cells, tfg KO CH12 cells were more sensitive toward ER stress induced by tunicamycin, monensin and proteasome inhibition or by expression of an ER-bound immunoglobulin (Ig) μ heavy (µH) chain. CH12 tfg KO B cells displayed more total LC3, lower LC3-II turnover and increased numbers and size of autophagosomes. Tandem-fluorescent-LC3 revealed less accumulation of GFP-LC3 in starved and chloroquine-treated CH12 tfg KO B cells. The GFP:RFP ratio of tandem-fluorescent-LC3 was higher in tunicamycin-treated CH12 tfg KO B cells, suggesting less autophagy flux during induced ER stress. Based on these data, we suggest that TFG controls autophagy flux in CH12 B cells and propose that TFG is a survival factor that alleviates ER stress through the support of autophagy flux in activated B cells and mature plasma cells.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Antibody; apoptosis; autophagy; autophagy flux; B cell; B1 B cell; endoplasmic reticulum stress; immunoglobulin; plasma cell; Trk-fused gene

TFG is upregulated during plasma cell differentiation and regulates apoptosis, ER stress and autophagy in a B cell line - Steinmetz, Tobit; Reimer, Dorothea; Urbanczyk, Sophia; Schlötzer-Schrehardt, Ursula; Winkler, Thomas; Jäck, Hans-Martin; Mielenz, Dirk (JOURNAL OF IMMUNOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-08